Karakteristik Fisikokimia dan Organoleptik Bakso Analog Berbahan Dasar Jamur Tiram Putih (Pleurotus ostreatus) dan Kale (Brassica oleracea var. sabellica) - Bernadetha Eden Krisdita; Vivi Nuraini; Nanik Suhartatik (Food Scientia : Journal of Food Science and Technology, 2023)
Mushroom and kale-based analog meatballs are one of diversified food products. White oyster mushrooms have good nutritional content and amino acid profiles equivalent to beef, while kale has good nutritional good content. The purpose of this research is to determine the best formulation of mushroom-based meatballs with addition of kale based on physical, chemical, and sensory properties. Completely Randomized Design (CRD) was used with the first factor being the comparison of white oyster mushrooms and tapioca flour (50%:50%, 65%:35%, 80%:20%), and second factor being addition of kale concentration (33%, 67%, and 100%). The research results that comply with SNI and have the highest level of consumer preference are as follows for chemical analysis: water content of 69.35%, ash content of 1.71%, fat content of 0.134%, protein content of 8.46%, carbohydrate content of 20.35%, and fiber content of 3.97%. Physical test results show a yield value of 85.11%, a texture elasticity value of 4.49%, and for colorimetric values, L* is 49.22, a* is -8.48, and b* is 18.59. Organoleptic test results preferred by panelists show a taste score of 4.23, a texture score of 3.47, and an appearance score of 3.91. Therefore, the best formulation is found in analog meatball A3B2.